2010
DOI: 10.3233/jad-2010-100552
|View full text |Cite
|
Sign up to set email alerts
|

S-Nitrosylation of DRP1 Does Not Affect Enzymatic Activity and is Not Specific to Alzheimer's Disease

Abstract: Abstract. Mitochondrial dysfunction and synaptic loss are among the earliest events linked to Alzheimer's disease (AD) and might play a causative role in disease onset and progression. The underlying mechanisms of mitochondrial and synaptic dysfunction in AD remain unclear. We previously reported that nitric oxide (NO) triggers persistent mitochondrial fission and causes neuronal cell death. A recent article claimed that S-nitrosylation of dynamin related protein 1 (DRP1) at cysteine 644 causes protein dimeriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
126
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 152 publications
(138 citation statements)
references
References 59 publications
(79 reference statements)
11
126
1
Order By: Relevance
“…14,22 We previously demonstrated that SNOC can trigger DRP1 S616 phosphorylation and mitochondrial fragmentation. 16,21 Furthermore, DRP1 is hyperphosphorylated on S616 in AD patient brains. 21,22 Because nanoceria were able to prevent Ab-induced mitochondrial fragmentation (Figure 4), we next investigated whether they could also inhibit DRP1 S616 phosphorylation, providing a potential mechanistic explanation for the observed mitochondrial preservation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…14,22 We previously demonstrated that SNOC can trigger DRP1 S616 phosphorylation and mitochondrial fragmentation. 16,21 Furthermore, DRP1 is hyperphosphorylated on S616 in AD patient brains. 21,22 Because nanoceria were able to prevent Ab-induced mitochondrial fragmentation (Figure 4), we next investigated whether they could also inhibit DRP1 S616 phosphorylation, providing a potential mechanistic explanation for the observed mitochondrial preservation.…”
Section: Resultsmentioning
confidence: 99%
“…16,21 Furthermore, DRP1 is hyperphosphorylated on S616 in AD patient brains. 21,22 Because nanoceria were able to prevent Ab-induced mitochondrial fragmentation (Figure 4), we next investigated whether they could also inhibit DRP1 S616 phosphorylation, providing a potential mechanistic explanation for the observed mitochondrial preservation. Neurons treated with either aged SNOC or nanoceria alone exhibited low baseline DRP1 S616 phosphorylation (Figure 5a).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations